CONCLUSION: SUMMARY OF ICHD MEETING, APRIL 1994 (Surfaces, 1994)
This document offers a conclusion to the papers and discussions that constituted the first meeting of the International Conference for Humanistic Discourse. These remarks review a number of the notions central to the project, including humanistic discourse, otherness, and translatability.